“Sentir o calor da terra, pra sentir que a gente está vivo ”: memória, identidade e territorialidade na vivência cotidiana do desastre da Samarco - Ana Beatriz Nogueira Pereira (2019)
This work aims to weave reflections on the processes related to the daily experience of sociotechnical disaster arising from the rupture of the dam belonging to mining company Samarco by people affected in the community of Paracatu, Mariana/MG. Disaster continues as a context of the victims' lives in the form of a chronic crisis triggered by the critical event, that is not restricted to the emergency period, but unfolds in time as a slow and continuous process, involving all dimensions of the lifeworld of people. With the experience of compulsory displacement, people daily construct new individual and collective identities, notions of belonging, community and place, in multiple movements of reterritorialization, which are also ways of being situated on a fragmented world. From narratives of suffering and resistance, we perceive how memory is reconfigured in the experience of disaster, and how categories such as time, place, community, freedom, home, identity, autonomy and others, get new meanings from this experience.